Leadership Challenges and Management of Community development Projects. A case of Sustainable Outcomes for Children and Youths -Kabale District - Andrew Kishokye, Muyambi (Kabale University, 2020)
The study was about leadership challenges and management of community development projects in Uganda, the case of TPO Uganda SOCY Kabale District. The study adopted a case study research design, which employed both quantitative and qualitative research approaches to collect and analyze data. The study targeted beneficiaries, who were children, youths and caregivers. A sample size of 136 participants was selected from a study population of 167 respondents using purposive, convenient and simple random sampling techniques. Both questionnaires and interviews comprised the data collection instruments. Descriptive and inferential statistics were used to analyze quantitative data while content analysis was used to analyze qualitative data. Using multiple regression analysis, the study found a weak but significant association between leadership challenges and management of community development projects. Communication had a significant positive effect on management of community projects while change management and financial resources had insignificant effects on management of community development projects. Citizen participation was found to affect management of community projects. Leadership challenges had a weak effect on the management of community development projects. The study recommended that TPO should provide, training to citizens on their role in management of community development projects, should ensure making their goals and objectives clear to the concerned citizens, should redesign their management strategies to cater for change management, and should adopt proper and sound financial management practices to remain accountable and transparent to both funders and beneficiaries